TEST FLOUR ANT NESTS INHIBITION (Myrmecodia pendans) AGAINST BACTERIA Escherichia coli and Salmonella IN INTESTINAL OF QUAIL ( Coturnix-coturnix japonica ) - Susan E Lumbangaol (Universitas Islam Balitar, 2018)
This research aims to know the influence of addition of Ant (Myrmecodia pendans) to drag power bacteria quail. The sample in this research was the quail as much as 250 quail. Basal feed consists of a mixture of yellow corn, soybeans for cake, MBM (meat bone meal) fish meal, pollard, dicalsiumposfhat, premix, cooking oil, and Dekstro lekso methionine. The addition of Ant consists of 5 treatments, namely control or P0 (0%), P1 (0,2%), P2 (0,4%), P3 (0,6%), as well as the addition of P4 (0,8%). The parameters observed inhibitory power is bacterial (Escherichia coli Bacteria Salmonella) and Total Plate Count (TPC). The research was designed using Random Design complete with 5 treatments and five replicates. The results of the analysis showed that the granting of Ant against test bacteria inhibitory power suggests that the addition of the Ant's nests significantly different (P<0,05) for bacteria Escherichia coli with an average power of drag is higheston treatment of P4 (0,8%) of 13,05 mm, whereas the drag power test Salmonella bacteria on average the highest inhibitory at the treatment power P2 (0,2%) of 12,21 mm. The addition of Ant against the test of Total Plate Count showed that increasing the giving of Ant can inhibit the bacteria in the gut quail but statistically not different either in the bacteria Escherichia coli Salmonella (P>0,05). Results of the study it was concluded that the higher the granting of Ant can maintain intestinal bacteria on growth performance of quail